DESIGN OF INFORMATION SYSTEMS MANAGEMENTEMPLOYEES BORROWING COOPERATIVES AEGIS OF THE REGIONAL OFFICE DEPARTMENT OF JUSTICE AND HAM WEST JAVA - R. Dipta Nugraha Pradhana; Don Elsafitra, SKom (Jurnal Sistem Informasi, 2003)
Cooperative aegis of the Department of Justice and Human Rights Officer of West Java is a business engaged in the process of saving and borrowing activities. Cooperative aegis of the Department of Justice and Human Rights Officer of West Java, aimed to promote the welfare of members in particular and society in general as well as fabric rebuild the national economy in order to realize a just and prosperous society based on Pancasila and the Constitution in 1945. In this study the authors tried to design a system that can be used in the context of lending and borrowing is done Cooperative aegis of the Department of Justice and Human Rights Officer of West Java so that existing work can be done quickly and accurately. Writing this took issue on Cooperative aegis of the Department of Justice and Human Rights Officer of West Java Regional Office of Justice located in Bandung.